(untitled) - Seeram, Euclid (Philadenphia, P.A., 2000)
British Columbia Institute of Technology. Provides up-to-date discussions of basic physics and instrumentation, clinical applications, and quality control. Examines significant developments in CT scanning in recent years. Covers latest developments in multislice applications such as 3D imaging, and CT angiography. Softcover. DLC: Tomography.
Keywords: Tomography